BIM Integration in Agile Scrum During The Design Phase - Chai, Changsaar; Tang, Joseph Tzuenyao; Chan, Szewen; Lee, Chia Kuang; Goh, Kaichen (Taylor's University, 2023)
The architectural, engineering, and construction (AEC) industry has explored various methods to lower project costs while improving quality and productivity. Building Information Modeling (BIM) and Scrum have demonstrated a high potential in assisting in achieving these objectives. BIM technology is essential as a technical container for the information model of a building project and as a new construction strategy that amalgamates other benefits outlined in the existing literature. This study examined the commonalities between Agile Scrum (AS) and Building Information Modeling (BIM) and explored the possibility of integrating BIM into the Agile Scrum framework, called BIM-Scrum. BIM-Scrum was formed by extracting core similarities between the study of BIM and Scrum. The design phase of the BIM project life cycle and its relevant components are extracted from CIDB Guide 5 for integration with Scrum. The "Collaboration Production of Information" phase and its relevant BIM components (Employer's Information Requirement (EIR), BIM Execution Plan (BEP), Task Information Delivery Plan (TIDP), Master Information Delivery Plan (MIDP) are extracted from the BIM life cycle to be synthesised with Scrum. Specific adjustments and refinements are recommended to allow BIM adaptation into Scrum during the adaptation process. Several interviews were conducted as part of the outcome review procedure, and content analysis was used to identify, characterise, and understand the interview data. The benefits of BIM-Scrum were identified, and adoption strategies were examined throughout the process. Finally, the BIM-Scrum framework was developed as a reference model for the Malaysian construction industry at the end of the research